The Relationship Between Copeptin And Cellular Oxidative Damage By Xanthine Oxidase, Heme Oxygenase-1 And Nitric Oxide Synthase In Metabolic Syndrome Patients - Mahdi, Athraa Adnan; Mahdi, Elham Abed (Medical Science Journal for Advance Research, 2023)
Background: Metabolic syndrome(MetS) is the medical term for a cluster of metabolic abnormalities that increases in individuals risk of T2DM and CVD. The component of MetS are glucose intolerance, obesity, hypertension and dyslipidemia. An insulin resistance is the key phase of metabolic syndrome constitutes the major risk factor for the development of diabetes mellitus. Objectives: The present study aimed to comprise Copeptin, Xanthine Oxidase, Heme Oxygenase-1 and Nitric Oxide synthase in addition to insulin resistance values and lipid profile among two study groups, metabolic syndrome patients and Controls group. Subjects: The present study included 50 metabolic syndrome patients and 50 individuals as healthy control. Methods: current study investigated the association between Copeptin, Xanthine Oxide, Heme Oxygenase and Nitric Oxide Synthase with development risk effect of endothelial dysfunction in MetS patients by applying ELISA kit method. Results: current work showed a highly significant variations among study groups, except for age.